(untitled) (African Multidisciplinary Journal of Research, 2022)
Parents are without a doubt, key stakeholders in schools, having the leading responsibility to guide the behaviour of their children. It is no wonder that they have been blamed for the development of deviant behaviour by adolescents in boarding schools. This descriptive study was conducted in Kiambu County, to find out how teenagers perceived their parents’ leadership style and if the boarding school experience may be a contributor to development of deviant behaviour. Out of the 13 Sub-Counties, the researcher purposively selected 3 - Githunguri, Limuru and Kiambu, representing more than 10%. At the time of the study, there were 109,782 high school students and the sample size was 100 students. The available population for the study was located in 102 boarding schools. The researcher stratified them by gender as follows; 46 mixed gender, 33 Girls’ and 23 Boys’ boarding schools and purposively selected one school from each strata. Using a structured questionnaire, the respondents gave their opinions on their parents’ leadership style, their boarding school experience and self-assessment of their behaviour. The data collected from the quantitative research showed that most teenagers perceived the leadership style of their parents to be authoritative, displaying balance in responsiveness and demandingness. However, most of them felt that their parents do not take their wishes into consideration before asking them to do something and many felt that they are not close to their parents. This aspect of lack of closeness to parents may in fact be leading to increased deviant behaviour. The researcher proposed that the Ministry of Education should help school administrators to increase parents’ involvement in boarding schools, to encourage closeness to their children in an effort to curb the development of deviant behaviour. Further, there is need to investigate the teacher’s leadership style. Keywords: Adolescents, Parents Leadership Style, Boarding School, Deviant Behaviour